Acute appendicitis during the COVID-19 lockdown: never waste a crisis!. Issue 1 (21st January 2021) - Podda, M; Pata, F; Pellino, G; Ielpo, B; Di Saverio, S
Abstract : 1. Whilst the number of Covid-19 cases increases, fewer patients present with appendicitis to the emergency department, and those who do, present with more advanced disease. 2. These findings are consistent with the hypothesis of a pre-hospital selection, with high rates of successful resolution of uncomplicated appendicitis following patients self-medication with antibiotics at home. 3. Patients admitted with suspected appendicitis during the pandemic are more likely to undergo preoperative imaging, which possibly explains the fall in negative appendectomy rate, especially in the UK.